Principles and Applications of Fat Grafting in Plastic Surgery - Abu-Ghname, Amjed; Perdanasari, Aurelia Trisliana; Reece, Edward M. (Seminars in Plastic Surgery, 2019)
Autologous fat transplantation has become increasingly popular in recent years. Its biocompatable properties and availability made it a widely used treatment modality for soft tissue augmentation and volume replacement in both reconstructive and aesthetic plastic surgery. Multiple protocols and clinical applications have been described in the literature, with wide variations in the harvesting, processing, and injection techniques. In this review, the authors will discuss the basic principles and clinical applications of fat grafting in plastic and reconstructive surgery. The article will then conclude with a discussion of fat grafting limitations as well as potential future applications, giving the reader a well-rounded understanding of autologous fat transfer.
Keywords: fat grafting; autologous fat transfer; lipofilling; adipose derived stem cells; volume augmentation; regeneration